Prognostic nutritional index and prognosis of patients with coronary artery disease: A systematic review and meta-analysis - Zhang, Shengjing; Wang, Huanfen; Chen, Saiya; Cai, Shengsheng; Zhou, Shigeng; Wang, Congling; Ni, Xiuyuan (Frontiers in Nutrition, 2023)
Background This review assessed if prognostic nutritional index (PNI) can predict mortality and major adverse cardiac events (MACE) in coronary artery disease (CAD) patients. Methods PubMed, Web of Science, Scopus, and Embase were searched up to 1st November 2022 for all types of studies reporting adjusted associations between PNI and mortality or MACE in CAD patients. A random-effect meta-analysis was conducted for PNI as categorical or continuous variable. Subgroup analysis were conducted for multiple confounders. Results Fifteen studies with 22,521 patients were included. Meta-analysis found that low PNI was a significant predictor of mortality in CAD patients as compared to those with high PNI (HR: 1.67 95% CI: 1.39, 2.00 I2 = 95% p < 0.00001). Increasing PNI scores were also associated with lower mortality (HR: 0.94 95% CI: 0.91, 0.97 I2 = 89% p = 0.0003). Meta-analysis demonstrated that patients with low PNI had significantly higher incidence of MACE (HR: 1.57 95% CI: 1.08, 2.28 I2 = 94% p = 0.02) and increasing PNI was associated with lower incidence of MACE (HR: 0.84 95% CI: 0.72, 0.92 I2 = 97% p = 0.0007). Subgroup analyses showed mixed results. Conclusion Malnutrition assessed by PNI can independently predict mortality and MACE in CAD patients. Variable PNI cut-offs and high inter-study heterogeneity are major limitations while interpreting the results. Further research focusing on specific groups of CAD and taking into account different cut-offs of PNI are needed to provide better evidence. Systematic Review Registration No CRD42022365913 https://www.crd.york.ac.uk/prospero/.